Employment effects of minimum wages in Europe revisited - Christl, Michael; Köppl-Turyna, Monika; Kucsera, Denes (Munich, 2015)
"The aim of this paper is to estimate the effect of minimum wage on employment rates taking into account potential nonlinearity. Focusing on three age groups, we find a significant nonlinear relationship between the minimum wage and employment for the young (15-24 years) and older working-age (55-64 years) groups, whereas for the prime-age workers (25-54 years) the minimum wage does not have a significant non-linear effect. Negative effect of the minimum wages on employment is stronger if the labor markets are otherwise strictly regulated and when workers are relatively unproductive."